Structural analysis of the β‐sheet edge of peptide self‐assembly using a model protein. Issue 7 (22nd February 2021) - Shiga, Shota; Makabe, Koki
Abstract: Peptides and proteins self‐assemble into β‐sheet‐rich fibrils, amyloid, which extends its structure by incorporating peptide/protein molecules from solution. At the elongation edge, the peptide/protein molecule binds to the edge of the amyloid β‐sheet. Such processes are transient and elusive when observing molecular details by experimental methods. We used a model protein system, peptide self‐assembly mimic (PSAM), which mimics an amyloid‐like structure within a globular protein by capping both edges of single‐layer β sheet (SLB) with certain domains. We constructed a PSAM variant that lacks the capping domain on the C‐terminal side to observe the structure of the β‐sheet edge of the peptide self‐assembly. This variant, which we termed PSAM‐edge, proved to be soluble with a monomeric form. Urea‐induced unfolding experiments revealed that PSAM‐edge displayed two‐state cooperative unfolding, indicating the N‐terminal capping domain and extended SLB folded as one unit. The crystal structure showed that SLB was almost completely structured except for a few terminal residues. A molecular dynamics simulation results revealed that the SLB structure was retained while the C‐terminal four residues fluctuated, which was consistent with the crystal structure. Our findings indicate that SLB is stable even when one side of the β‐sheet edge is exposed to a solvent. This stability may prevent the dissociation of the attached peptide from the peptide self‐assembly. Because of the scarcity of SLB proteins with exposed β‐sheet edges in nature, successful construction of the PSAM‐edge expands our understanding of protein folding and design.